2021
DOI: 10.1186/s12903-021-01429-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, radiographical and histological evaluation of alveolar ridge preservation with an autogenous tooth derived particulate graft in EDS class 3–4 defects

Abstract: Background The shrinkage of alveolar bone dimensions after tooth extraction is a well-known issue. This clinical phenomenon poses a challenge for clinicians aiming at implant-prosthetic treatment. BonMaker® ATB is a novel autogenous bone grafting material, produced by the mechanical and chemical processing of natural teeth. This pilot case report aims at providing a clinical, radiographical, and histological evaluation of the safety and efficacy of Bonmaker ATB powder in the treatment of EDS cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 26 publications
0
8
0
1
Order By: Relevance
“…Radoczy-Drajko et al demonstrated that AUTO-BG when used as a graft material for socket preservation leads to a mean bone loss of 15% in the horizontal dimension (maximum at the coronal portion and minimum at the apical) with negligible loss in the vertical dimension. These findings show that successful results can be obtained with AUTO-BG with functional restoration using implants later on [ 86 ].…”
Section: Clinical Applications Of Auto-bgmentioning
confidence: 79%
“…Radoczy-Drajko et al demonstrated that AUTO-BG when used as a graft material for socket preservation leads to a mean bone loss of 15% in the horizontal dimension (maximum at the coronal portion and minimum at the apical) with negligible loss in the vertical dimension. These findings show that successful results can be obtained with AUTO-BG with functional restoration using implants later on [ 86 ].…”
Section: Clinical Applications Of Auto-bgmentioning
confidence: 79%
“…To date, many studies have confirmed that ATGP could be used as an alternative option, providing excellent biocompatibility without causing an immune response, contagion, or reaction to a foreign material in socket preservation, alveolar repair, and different kinds of bone augmentation in dental clinics [ 15 , 20 27 ]. This study reached a similar conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…(Fig. 1 ) [ 15 ]. The M3 extraction socket was filled and compacted in layers with freshly prepared ATGP.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Napjainkban a dentalis implantátumok, műgyökerek behelyezése, illetve az állcsontok fogmedernyúlványának sorvadása esetén a csont felépítése a fogászati rehabilitáció napi gyakorlatává vált. A fogmedernyúlvány felépítése mind a technikai megoldások, mind a felhasznált csontpótló anyagok és a csontpótlásokat fedő mesterséges membránok szempontjából sokszínű, aktívan kutatott, folyamatosan fejlődő és egyre biztatóbb eredményeket nyújtó terület [1][2][3][4][5]. A felhasznált anyagok fejlődése és sokrétűsége ellenére a mai napig a legtöbben a saját csont alkalmazását tekintik a "gold standard" eljárásnak [6][7][8], ugyanakkor megjegyzendő, hogy Trimmel és mtsai legújabb metaanalízisükben ettől eltérő következtetésre jutottak [9].…”
unclassified